Family functioning and resilience in patients with noncommunicable diseases of a public hospital in Metropolitan Lima - Céspedes Felix, Moises (2018)
Objective: of the present investigation was to: study the relationship between family functioning and resilience variables in patients with noncommunicable diseases of a public hospital in Lima. Material and Methods: of the research was non-experimental, cross-sectional and correlational in scope. The model of family functioning on which we worked was the Circumplex family system model by Olson, Russell and Sprenkle (1979). The scale used to measure family functioning was the Family Cohesion and Adaptability Assessment Scale (FACES III) and to measure resilience, the Resilience Scale developed by Wagnild and Young (1993) was used, which consists of five dimensions. The sample consisted of 109 patients. In the Results it was found that family functioning is not related to resilience (x2 = 5.972, p> .05). Therefore, it is Conclussion: that whatever the level of family functioning, it is possible that the patient is resilient; since there are individual factors that intervene in the development of resilience.